Behavioural indicators of translators’ decisional styles in a translation task: A longitudinal study - Lehka-Paul, Olha (Yearbook of the Poznan Linguistic Meeting, 2020)
Translation Process Research defines translation as a decision-making process, but a plethora of studies has demonstrated that there is high individual variation in the translators’ styles of making decisions. The present interdisciplinary empirical study combines the theory of personality types and translation process research in order to identify the behavioural indicators that characterise translators’ decisional styles at the stage of end revision, where final decision-making takes place. As based on previous research, such indicators as the duration of end revision, pause length and number, the number of deleted characters and the types of corrections introduced at the stage of end revision may comprise the behavioural variables that define the translators’ styles of decision-making. The analysis of the data shows that two distinct behavioural styles may be distinguished, and their nature lies in the translators’ individual preferences for one of the two dichotomous psychological functions responsible for decision-making.